STUDI PENERAPAN TEKNOLOGI TEPAT GUNA TERHADAP PERUBAHAN SOSIAL NELAYAN KARAMBA DI KELURAHAN PEMBUANG HULU I, KECAMATAN HANAU, KABUPATEN SERUYAN, PROVINSI KALIMANTAN TENGAH - Yos Andy Tangkasiang; Akhmad Syarif (JURNAL SOCIOPOLITICO, 2022)
Although opportunities for transfer and mastery of various technologies are very possible, it does not mean that all technologies developed in Indonesia can have a positive influence, but can also have a negative effect. Every technology that is transferred and developed must be adjusted to cultural preferences, social circumstances, and other environmental conditions. As in the area of Pembuang Hulu I Subdistrict, Hanau Subdistrict, Seruyan Regency, Central Kalimantan Province, karamba technology has been widely known by its people, and the appropriate technology applied is a sharpening of the technology that has been used by local communities. As a result of the implementation of this technology, there have been social changes experienced by the population consciously or unconsciously, resulting in a consumptive lifestyle due to an increase in income.